Four-year longitudinal culinary and lifestyle medicine track for undergraduate medical students: development and implementation - Madison Humerick; Rosemarie Cannarella Lorenzetti; Melody M. Phillips; William D. Lewis; Emma M. Eggleston (Medical Education Online)
The importance of culinary and lifestyle medicine education to combat the growing burden of chronic disease is gaining recognition in the United States. However, few medical schools offer in-depth training with a 4-year longitudinal track. The Culinary and Lifestyle Medicine Track (CLMT) is a 4-year curriculum thread created at West Virginia University School of Medicine to address the need for comprehensive culinary and lifestyle medicine education. CLMT teaches concepts of healthy nutrition, physical activity, stress management, and restorative sleep. CLMT students complete approximately 300 h of in-person and virtual culinary and lifestyle medicine education, including hands-on teaching kitchens, distributed over the preclinical and clinical years. Students are selected into the track prior to matriculation after an application and interview process. The students have exceeded expectations for scholarly and community activity. Track graduates have entered into primary care as well as specialty and surgical residencies, demonstrating that lifestyle education plays a role for students interested in a wide range of careers. Exit survey responses from learners reflected tangible and intangible benefits of participation and offered constructive feedback for improvement. Presented here are the components of the curricular design, implementation, and initial outcomes.